Antarctophthirus ogmorhini Enderlein 1906 - Leonardi, Maria Soledad; Palma, Ricardo Luis (Zenodo, 2013)
Antarctophthirus ogmorhini Enderlein, 1906 “ Echinophthirius setosus ” Rothschild, 1902: 224. Not Echinophthirius setosus (Burmeister, 1838) = Echinophthirius horridus (Olfers, 1816). Antarctophthirus ogmorhini Enderlein, 1906: 662, figs 1–2. Neumann 1907: 13, in part; Dalla Torre 1908: 17; Enderlein 1909: 508, pl. 57, pl. 60, figs 181–182; Neumann 1909: 537; Cummings 1916: 172; Ferris 1916a: 183; Tillyard 1926: 135; Freund 1928: 19, figs 12–13; Ferris 1934: 486, figs 282–283; Harrison 1937: 11; Thompson & Plomley 1938: 116, 124; Hopkins 1949: 509; Séguy 1951: 1381; Ferris 1951: 73, fig. 31; Gressitt & Weber 1959: 447; King 1964: 137; Murray 1964: 243; Murray et al. 1965: 761, fig. 1, pls 1–2; Murray 1967: 190; Clay & Moreby 1967: 166, fig. 179; Calaby 1970: 107, fig. 5.1; Clay & Moreby 1970: 220; Gressitt 1970: 329; Dailey & Brownell 1972: 542; Kim et al. 1975: 547; Arthur 1976: 170; Murray 1976: 93, figs 4.1–4.3; Ledger 1980: 206, fig. 214; Marshall 1981: 175, 249, 292 fig. 8.4; Kim 1982a: 408, fig.; King 1983: 203; Rounsevell & Horne 1986: 312, 323; Kim 1988: 108; Calaby & Murray 1991: 69, fig. 3.1; Durden & Musser 1994a: 7; Durden & Musser 1994b: 141; Barker 1996: 237; Price & Graham 1997: 119; Pajot 2000: 32, fig. 4; Mehlhorn et al. 2002: 651, figs 1–17; King 2005: 234; Palma 2010: 409. Antarctophthirius [sic] ogmorhini Enderlein, 1906; Ass 1934: 103. Misspelling. Antarctophthirus sp.; Harrison 1937: 13 [ex Leptonychotes weddelli , Adelie Land, Antarctica]; Clay 1940: 296 [ex Leptonychotes weddelli , W. Graham Land, Antarctica]. Antarctophthirus ? ogmorhini (Enderlein) [sic]; Hopkins 1949: 510. Antarctophtirus [sic] ogmorhini Paulian 1953: 123, 232. Misspelling. Antarctophthirus ogmorphini [sic]; Marshall 1981: 145. Misspelling. Type host. Hydrurga leptonyx (Blainville, 1820) —Leopard seal. Type locality. Victoria Land and Booth Wandel Island, Antarctica. Type specimen/s data. Syntypes Ƥ in NHML (3 BM 1901-284, Ƥ BM 1901-254). Other hosts. Leptonychotes weddellii ...